Integrating Dryland Agriculture into Student Worksheets to Enhance Students’ Numeracy Skills - Yohanis Ndapa Deda; Stanislaus Amsikan; Benidiktus Tanujaya (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Integrating local wisdom into student worksheets enhances the meaningfulness and cultural relevance of mathematics learning. However, few student worksheets integrate local wisdom related to dryland agriculture—a practice central to the socio-cultural and economic life of the semi-arid North Central Timor District—to support students’ numeracy skills. Dryland agriculture provides rich real-life quantitative contexts that are highly relevant for developing students’ numeracy competencies. Therefore, this study aimed to develop and evaluate student worksheets grounded in local dryland agriculture using a research and development approach with Tessmer’s formative evaluation model involving 26 purposively selected eighth-grade students. Data were collected through interviews, questionnaires, and numeracy tests, then analyzed using interactive qualitative analysis alongside descriptive and inferential statistics. The results indicate that the developed worksheets are valid (77.67%) and practical, as evidenced by an 80.44% positive student response rate. Furthermore, the field test results demonstrated the effectiveness of the student worksheets, as indicated by a significant improvement in students’ numeracy scores from pretest to posttest. These findings suggest that culturally grounded, context-based student worksheets can effectively enhance students’ numeracy development in rural dryland contexts while also supporting students’ readiness for national mathematics assessments.